Evidences of Multicomponent Structure of the Migratory Stock and Morphological Distinctions of Shads from the Genus Alosa (Clupeaformes, Alosiinae) of the Sea of Azov - Mezhzherin, S.V.; Vernygora, O.V. (Вестник зоологии, 2013)
Migratory stocks of shads passing through the Kerch strait during their seasonal migrations consist of three groups of specimens, that can be identified based on the number of gill rakers on the first arch. These are so called Kerch shad A. maeotica (50.2 %), Pontic shad A. immaculata (48.7 %) and Caspian shad A. caspia (1.1 %). This ratio of species in the region remains stable for the last 60 years. Populations of Kerch and Pontic shads have similar age structure and sex ratio with a shift toward females 52–54 %. Specimens of A. maeotica have greater linear size and weight than those of A. immacuta, that indicates higher growth rate of the former. Analysis of 26 body measurements shows definite differences between these shads in their absolute features, there are also some differences in the proportions of the head. Nevertheless, degree and reproducibility of interspecific differences during various periods of time, do not allow for the reliable discrimination of specimens of these species assumed by some researchers. Миграционные стада пузанковых сельдей, проходящие в период сезонных миграций через Керченский пролив, состоят из особей трёх групп, которые можно идентифицировать по числу жаберных тычинок на 1-й дуге. Это так называемая керченская сельдь, A.?maeotica (50,2 %), черноморско-азовская сельдь, A. immaculata (48,7 %), и пузанок, A. сaspia (1,1 %). Такое соотношение между этими видами в регионе остаётся стабильным на протяжении последних 60 лет. Популяции керченской и черноморско-азовской сельдей имеют одинаковую возрастную структуру и соотношение полов, при котором самки составляют 52–54 %. Особи A. maeotica отличаются от A. immaculata большими линейными размерами и массой, что свидетельствует о более высоком темпе их роста. Использование 26 промеров тела показывает определённые различия между этими сельдями по абсолютным признакам, также отмечаются некоторые различия и в пропорциях головы. Тем не менее масштаб и низкая воспроизводимость межвидовых различий в разные периоды не позволяют надежно дискриминировать особей этих предполагаемых некоторыми исследователями видов.